LEGAL ASPECTS OF THE LEGAL STATUS OF COMPANIES OR BUSINESS ENTITIES IN BUSINESS ACTIVITIES - Rahmawati Hutagalung (CV. Radja Publika, 2026)
Companies are always connected with third parties and want to protect honestly run companies (